Management Practice of Women in Entrepreneurship Activities of Micro Enterprise Running in Parbat District, Nepal - Dhaubhadel, Sarita; Modi, Devendra Kumar (Nepal Journal of Multidisciplinary Research, 2022)
Correction: On 21st September 2022 the co-author was changed from Dr D.K. Maheshwari to Prof. Dr. Devendra Kumar Modi Micro-enterprises are small-scale businesses run by low-income people with government or non-government assistance. It helps people manage their daily requirements by improving their quality of life and adding value to the local economy in underdeveloped countries. They provide many small-scale jobs, raise income, increase purchasing power, and strengthen the country's economy. The major goal of this research was to find out how women micro-entrepreneurs may run their businesses as under-represented and seemingly stigmatized minority business owners. Micro businesses make managerial decisions based on individual tastes and priorities. The study discovered that the true meaning of micro-enterprise management goes beyond the standard business semantics. The study included 384 women from the Parbat district of Nepal who worked in micro-enterprises. According to the study, the participation of family members has a substantial impact on the success of a micro business. The results suggest that 99 percent of the women agreed the involvement of family members and supporters to run the enterprise. Similarly 74.50 percent women agreed that they received training to run their enterprise.